Effects of Angiopoietin-1 on Hemorrhagic Transformation and Cerebral Edema after Tissue Plasminogen Activator Treatment for Ischemic Stroke in Rats - Kawamura, Kunio; Takahashi, Tetsuya; Kanazawa, Masato; Igarashi, Hironaka; Nakada, Tsutomu; Nishizawa, Masatoyo; Shimohata, Takayoshi (PLOS ONE, 2014)
An angiogenesis factor, angiopoietin-1 (Ang1), is associated with the blood-brain barrier (BBB) disruption after focal cerebral ischemia. However, whether hemorrhagic transformation and cerebral edema after tissue plasminogen activator (tPA) treatment are related to the decrease in Ang1 expression in the BBB remains unknown. We hypothesized that administering Ang1 might attenuate hemorrhagic transformation and cerebral edema after tPA treatment by stabilizing blood vessels and inhibiting hyperpermeability. Sprague-Dawley rats subjected to thromboembolic focal cerebral ischemia were assigned to a permanent ischemia group (permanent middle cerebral artery occlusion; PMCAO) and groups treated with tPA at 1 h or 4 h after ischemia. Endogenous Ang1 expression was observed in pericytes, astrocytes, and neuronal cells. Western blot analyses revealed that Ang1 expression levels on the ischemic side of the cerebral cortex were decreased in the tPA-1h, tPA-4h, and PMCAO groups as compared to those in the control group (P = 0.014, 0.003, and 0.014, respectively). Ang1-positive vessel densities in the tPA-4h and PMCAO groups were less than that in the control group (p = 0.002 and <0.001, respectively) as well as that in the tPA-1h group (p = 0.047 and 0.005, respectively). These results suggest that Ang1-positive vessel density was maintained when tPA was administered within the therapeutic time window (1 h), while it was decreased when tPA treatment was given after the therapeutic time window (4 h). Administering Ang1 fused with cartilage oligomeric protein (COMP) to supplement this decrease has the potential to suppress hemorrhagic transformation as measured by hemoglobin content in a whole cerebral homogenate (p = 0.007) and cerebral edema due to BBB damage (p = 0.038), as compared to administering COMP protein alone. In conclusion, Ang1 might be a promising target molecule for developing vasoprotective therapies for controlling hemorrhagic transformation and cerebral edema after tPA treatment.